Effect of Proprioception Exercise versus Focused Regimen Exercise on Balance and Quality of Life in Subjects with Diabetic Neuropathy. - PradhapSankar, V.; Janani, R.; Abraham, M. Manoj (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Diabetic peripheral neuropathy is a polyneuropathy that can cause damage to the peripheral nerve fibers, sensorimotor and autonomic nervous system. Neuropathy causes somatosensory dysfunction of the lower extremities, such as decreased ankle position and vibration sensations. The sensation of the skin on the feet and the proprioceptive sense are two important factors in standing balance, postural control and coordination. As this condition progresses, this can lead to increased postural sway, gait disturbance, abnormal neuromuscular control and increased reaction time leading to falls in balance impaired patients. Objective: To determine the effect of proprioception exercise versus focused regimen exercise on balance and quality of life in subjects with diabetic neuropathy. Methods: 20 Subjects with diabetic neuropathy of both genders, in the age group of 40 - 60 years were conveniently assigned into 2 groups. Group A (n = 10) received Proprioception exercise and Group B (n = 10) received Focused regimen exercise, 3 sessions a week for 8 weeks. Balance and quality of life were evaluated with Berg Balance Scale and SF - 36 Survey questionnaire. Results: The difference in the post-test mean scores of group A and group B in Berg Balance Scale was 32 and 28.3 and SF - 36 Survey questionnaire was 61.4 and 56.6 respectively. The result showed a significant improvement in Group A than in Group B at p < 0.0001. Conclusion: Therefore, the study concludes that the Proprioception exercise training is better management to improve balance and quality of life in subjects with diabetic neuropathy.